Outcome of Forearm Shaft Fractures in Adults Treated by Dynamic Compression Plate (DCP) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To evaluate the clinical and radiographic outcome after open reduction and internal fixation of the forearm diaphyseal fractures by Dynamic Compression plate (DCP).Methodoligy: We prospectively, investigated the clinical and radiographic outcome for 94 adult patients with 154 forearm shaft fractures. The study groups include 70 males, and 24 females. Patients were treated by open reduction and internal fixation with small DCP and followed up for 24 months. Time of union, rate of union, complications and outcome were assessed according to the modified system of Price and Daruwalla Score.Results: Out of 154 fractures 149 (94.155%) had united at a mean time of 15.4 weeks (range 11-26weeks), there was 02(3.08%) superficial infection that healed by debridement and antibiotics, and 01(1.54%) deep infection which caused to delayed union and underwent reoperation, including change of implant and bone graft. Two (3.08%) radial nerve injuries occurred after operation, full recovery in one and partial in another patient was observed after 6 months. Excellent and good results were seen in 40 (66.7%) and 20 (33.3%) of the patients with both bone fractures, in radius Excellent and good results were seen in 16(80%) and 04(20%) patients, in ulna Excellent and fair 14(85.75%) and 2(14.25%) of adults forearm shaft fractures with conventional 3.5 mm DCP was associated with a high rate of success. The results with this type of plate are comparable with the never and more expensive implants.Key Words: diaphyseal forearm fracture, Radius, Ulna, Open Reduction, Internal Fixation, Dynamic Compression Plate.